Investigation of Minor and Ordinary Assault Offenses: Case Study at Polsek Medan Timur, Indonesia - Nelly Tiurma Br. Marpaung; D. Debora (Manunggal Halim Jaya, 2026)
Criminal assault remains one of the most common offenses encountered in society, often triggered by minor disputes that escalate into physical harm. This study aims to investigate the process of handling minor and ordinary assault offenses at the East Medan Police Sector and to analyze the legal distinctions between Article 351, paragraph (1), and Article 352 of the Indonesian Criminal Code. This research employs a normative-empirical method, combining statutory analysis with field data obtained through interviews, observations, and documentation. The findings reveal that differences in determining the severity of injuries often lead to inconsistencies between investigators and prosecutors, primarily due to the absence of clear legal criteria for injury classification. The study also shows that minor assault cases constitute the majority of reports handled, with restorative justice frequently used as a settlement mechanism. Investigators rely heavily on medical reports and victim statements to determine the appropriate article to apply. This research highlights the need for more explicit legal norms regarding injury categories and stronger coordination among law enforcement institutions to ensure consistent and fair handling of assault offenses.